If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 3x + -18 Reorder the terms: 4 = -18 + 3x Solving 4 = -18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + -3x = -18 + 3x + -3x Combine like terms: 3x + -3x = 0 4 + -3x = -18 + 0 4 + -3x = -18 Add '-4' to each side of the equation. 4 + -4 + -3x = -18 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = -18 + -4 -3x = -18 + -4 Combine like terms: -18 + -4 = -22 -3x = -22 Divide each side by '-3'. x = 7.333333333 Simplifying x = 7.333333333
| 66-(7x+6)=7(x+2)+x | | 12x-x^2=12.8 | | 22r+18=32r-24 | | a+4a-21=0 | | x^2+49x-380=0 | | -4v+6v=-16 | | 4x^4+2x^3-39x^2+43x-10=0 | | 6x-8x+10=87-21+10x | | x-(-11)=18 | | -7(2t+3)=-35 | | s*4-46=-2 | | 49x+1.5=25x+3 | | 3x-7-4x+11=6x-3 | | 12a+12a+7a+7a= | | 40c+8=48c-20 | | -30=-5+5 | | 3x-7-4x+11=6x-7 | | 2f=10 | | 10+5(a-3)=9-2a | | tg(2x)=0.6 | | 2z^2-15z+7=0 | | 7(x-6)=56 | | x^2-10x+6=1 | | 7(3s+4)=133 | | 3z+3z+4z+3+4z+3=132 | | 3f=9 | | 8(2l+8)=112 | | 3x+1+1x+11=180 | | 5*(5*(5*(5+4)+3)+2)+1= | | x+13=111 | | 6k+k-3k+3=19 | | 7h+18=214 |